TINJAUAN YURIDIS PERJANJIAN PENGIKATAN JUAL-BELI TANAH YANG DIBUAT OLEH NOTARIS - Ginting, Juliati BR (The Juris, 2018)
Basically, the legal force of the contract of sale and purchase agreement of land rights made by notaries is very strong, because the deed is an authentic deed. Provision of irrevocable powers in the land sale and purchase agreement. Likewise, the protection of the law against the fulfillment of the party’s rights if one party to default in the sale and purchase agreement depends on the strength of the agreement made ie if Privately Made Deed then still the protection is not strong but if the agreement in front of the notary then the deed has the power of executorial.